Use of spinal cord stimulation for the treatment of post total knee arthroplasty pain. Issue 3 (September 2020) - Urits, Ivan; Markel, Michael; Vij, Neeraj; Ulanday, Josh; Machek, Megan; An, Daniel; Charipova, Karina; Gress, Kyle; Herman, Jared A.; Kaye, Alan D.; Viswanath, Omar
Abstract : Total knee arthroplasty (TKA), a common elective surgical procedure, is indicated in patients with knee pain that becomes refractory to nonsurgical interventions, such as weight loss, physical activity, physical therapy, and pharmacologic treatment. However, postoperative chronic pain is frequently reported and may lead to opioid use and dependence. Due to the increasing concern of the overuse of opioids in medical treatments, a search for other viable options is recognized. As a consequence, alternative therapies, such as transcutaneous electrical nerve stimulation (TENS), pulsed radiofrequency (PRF), and spinal cord stimulation (SCS) are being tried to potentially replace traditional opioid use in treating persistent postsurgical pain (PPSP), thus reducing opioid dependence across the nation. Here, we provide a brief overview of persistent pain following TKA procedures, with a particular emphasis on the role of promising therapies, such as TENS, PRF, and SCS for the treatment of post-TKA pain.